2019
DOI: 10.1021/acs.bioconjchem.8b00761
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugated Oligonucleotides: Recent Developments and Therapeutic Applications

Abstract: Oligonucleotide-based agents have the potential to treat or cure almost any disease, and are one of the key therapeutic drug classes of the future. Bioconjugated oligonucleotides, a subset of this class, are emerging from basic research and being successfully translated to the clinic. In this review, we first briefly describe two approaches for inhibiting specific genes using oligonucleotides -antisense DNA (ASO) and RNA interference (RNAi)followed by a discussion on delivery to cells. We then summarize and an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
175
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(178 citation statements)
references
References 167 publications
0
175
0
Order By: Relevance
“…In this context, ONs represent a promising strategy to restore the resistant bacteria sensitivity to current antibiotics treatments, and in particular 3GCs 20,22 . However, despite their high potential, the cellular uptake of oligonucleotides remains one of the key steps for eliciting their biological activity, as the targeted mRNAs are located inside the cells 21,23 . Recently, we demonstrated that Lipid-oligonucleotide conjugates improve cellular uptake and efficiency of antisense in eukaryotic prostate cancer cells 24 .…”
mentioning
confidence: 99%
“…In this context, ONs represent a promising strategy to restore the resistant bacteria sensitivity to current antibiotics treatments, and in particular 3GCs 20,22 . However, despite their high potential, the cellular uptake of oligonucleotides remains one of the key steps for eliciting their biological activity, as the targeted mRNAs are located inside the cells 21,23 . Recently, we demonstrated that Lipid-oligonucleotide conjugates improve cellular uptake and efficiency of antisense in eukaryotic prostate cancer cells 24 .…”
mentioning
confidence: 99%
“…Now, there are several efficient strategies for TNA delivery to the liver: lipid nanoparticles of various compositions and GalNAc conjugates that demonstrated exclusive delivery to hepatocytes via ASGP receptors, even in the case of subcuta-neous injections. 156,157 Heavily modified GalNAc-TNA conjugates can efficiently downregulate targets in the liver for up to 7 to 8 months after a single subcutaneous injection. 158 The main issue for TNA applications is off-target effects generated by downregulation of targets with partial complementarity to TNA.…”
Section: Targeting Mirna and Lncrna In The Livermentioning
confidence: 99%
“…This leads to peak broadening and increased difficulty in separating structurally very similar impurities. In a previous study [20] of PSmodified ONs, we found that selecting the ion-pair reagent in the eluent was crucial for the diastereomer selectivity and the use of trimethylammonium acetate followed by triethylammonium acetate resulted in the best selectivity. On the other hand, the use of tributyl ammonium acetate in the eluent suppressed diastereomer selectivity [20].…”
Section: Introductionmentioning
confidence: 95%
“…Much research has been focused on developing chromatographic methods to analyze phosphorothioate (PS)-modified ONs, which was recently summarized in a comprehensive review, including discussion about column chemistry and ion-pairing reagents [7]. A common separation challenge is the partial separation of the diastereomers introduced by the PS modification [7,[18][19][20]. This leads to peak broadening and increased difficulty in separating structurally very similar impurities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation